Camping catastrophe - Klein, Abby.; McKinley, John, 1956- (New York : Blue Sky Press, 2008)
First-grader Freddy, who is afraid of the dark, is apprehensive about going on a wilderness camping trip.
Keywords: Camping -- Juvenile fiction; Fear of the dark -- Juvenile fiction